14C Measurements Elucidate Isotopic Differences between Nails and Hair in Modern Humans. Issue 1 (2014) - De La Torre, Hector A Martinez; Ormsby, Kaelyn M; Fuller, Benjamin T; Santos, Guaciara M
Abstract : In forensic sciences, radiocarbon found in modern human nails and hair is evaluated to determine the year of death. However, 14 C analyses presented herein of fingernails and hair from the same infant demonstrated 14 C values of hair that were lower than would be expected (e.g. depleted relative to the fingernails by at least 10‰). These results prompted a series of 14 C measurements on infant hair strands, fingernails, and infant shampoo, which suggested the presence of C contamination due to cosmetic products. To further evaluate these discrepancies, several hair strands and fingernail samples from multiple donors were collected, pretreated by several approaches, and measured using isotopic analysis (δ 13 C, δ 15 N, and C/N as well as 14 C accelerator mass spectrometry). SEM images of the surface of chemically pretreated hair strands were also taken to inspect the performance of the chemical pretreatments applied. Our 14 C and stable isotope results show that modern human hair is likely contaminated with fossil-fuel-derived carbon, which is found in most hair care products. Currently, the various chemical pretreatments available in the literature and presented herein show that it is not possible to completely remove foreign carbon contaminates. Thus, the human 14 C and δ 13 C values between keratinous tissues (fingernails and hair) arc not in agreement. From these observations, it becomes apparent that isotopic interpretations using human hair should be used with extreme caution and additional work is needed for its use in forensic and dietary research.